2008
DOI: 10.1590/s1413-81232008000700024
|View full text |Cite
|
Sign up to set email alerts
|

Padrão de consumo de medicamentos sem prescrição médica na cidade de Porto Alegre, RS

Abstract: Self-medication is a very common practice not only in Brazil but also in other countries. It is defined as medication of oneself without med-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
48

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 9 publications
2
8
0
48
Order By: Relevance
“…Overall, women had a higher self-medication prevalence compared to men, as previously demonstrated for the consumption of prescription drugs, a finding consistent with other studies conducted throughout Brazil (Loyola Filho et al, 2002;Ribeiro et al, 2008;Vitor et al, 2008). Self-medication was strongly correlated to age group, with elderly persons having a high prevalence of prescription drugs and low prevalence of self-medication.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, women had a higher self-medication prevalence compared to men, as previously demonstrated for the consumption of prescription drugs, a finding consistent with other studies conducted throughout Brazil (Loyola Filho et al, 2002;Ribeiro et al, 2008;Vitor et al, 2008). Self-medication was strongly correlated to age group, with elderly persons having a high prevalence of prescription drugs and low prevalence of self-medication.…”
Section: Discussionsupporting
confidence: 89%
“…Most interviewees claimed being aware of the risks associated with self-medication, demonstrating that lack of knowledge about medications was insufficient to abolish self-medication and that orientation of the population is insufficient to reduce inappropriate use of medicines, as discussed in other papers (Arrais et al, 1997;Flores, Benvegnú, 2008;Vitor et al, 2008). Importantly, only a small proportion of individuals were prevented from buying drugs without prescriptions, a fact that contributes to self-medication and corroborates results of other studies calling for greater control and restrictions on the dispensing of drugs in pharmaceutical establishments (Pereira et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…7 Some studies concluded that fertile women are the individuals who more often use drugs without a prescription. 4,7,10 Therefore, nursing mothers belong to the age group at the highest risk of self-medicating. In Itaúna, 52.4% of the nursing mothers practiced self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nevertheless, several studies have demonstrated that self-medication is a reason of great concern, especially in Brazil. [4][5][6][7][8][9][10] Arrais et al 7 found the highest frequency of self-medication among Brazilian women between 16 and 45 years old, an age group with potential to breastfeed. However, the use of drugs by women during lactation was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de medicamentos sem a prescrição por um profissional habilitado, cabendo ao paciente decidir qual medicamento utilizar é conhecido como automedicação 4 . Essa prática quando realizada pelos idosos pode ter consequências ainda mais graves 5 .…”
unclassified